Proteção contra a infecção por Leishmania (Leishmania) amazonensis pela imunização de camundongos BALB/c com peptídeos sintéticos selecionados por phage display e spot synthesis - Miguel Angel Chavez Fumagalli (2008)
Leishmania amazonensis is one of the major etiologic agents of a broad spectrum of clinical forms of leishmaniasis and has a wide geographical distribution in Americas, which overlaps with the areas of transmission of many other Leishmania species. In this work, the protective efficacy induced by immunization with a polymer originatedfrom two synthetic peptides selected by Phage Display and Spot-Synthesis techniques was evaluated in BALB/c mice against L. amazonensis challenge infection. Phagedisplayed peptides were screened using IgGs antibodies purified from serum samplesof dogs with active visceral leishmaniasis. Three clones were found to interact with antibodies and the corresponding synthetic peptides were synthesized by the Spot-Synthesis method on cellulose membrane. In the screening using the peptides, two of them (named 11H and 12A) were recognized in Spot-ELISA and, synthesized in their soluble form, covalently conjugated with glutaraldehyde originating a polymer ofapproximately 30 kDa and these was used as immunogen. Immunization with polymer was able to induce a Th1 immune response prior to infection. After challenge infection, a sustained IFN- production, low levels of IL-4, IL-10 and specific antiparasite antibodies were detected in this mices. In contrast, mice of the control groups displayed low levels of IFN- and high levels from IL-4, IL-10 and specific anti-parasiteantibodies. We concluded that the use of synthetic peptides can be an alternative approach to generate vaccines against American Tegumentary Leishmaniasis.